Development of Mathematical Logic Practicum Module Based on PhET Simulation to Improve Students' Reasoning Ability - Prihatin, Iwit; Oktaviana, Dwi (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2021)
This study aims to produce a mathematical logic praticum module based on a PhET simulation to improve students rational, practical, and effective reasoning skills. This research is a resrarch development of Borg and Gall with 7 stages. Valid products are seen from the results of expert validation, practical products are seen from the results of the questionnaire, while effective products are seen from the results of trials. The results of the validation of the experts obtained very valid criteria with a mean of 88,72%. The results of the student response questionnaire obtained results of 90,16%, with very practical criteria. The test results obtained the Sig. (2-tailed) paired t test is 0,000 less than 0,05, which means that there are differences in students’ mathematical reasoning abilities after using a development product in the form of a mathematical logic practicum module based on PhET simulation. It can be concluded that the mathematical logic practicum module based on PhET simulation is feasible to be used as a manual for mathematical logic practicum and can improve students reasoning abilities.Penelitian ini bertujuan untuk menghasilkan modul praktikum logika matematika berbasis PhET simulation untuk meningkatkan kemampuan penalaran mahasiswa yang valid, praktis, dan efektif. Penelitian ini adalah penelitian pengembangan Borg and Gall dengan 7 tahap. Produk valid dilihat dari hasil validasi ahli, produk praktis dilihat dari hasil angket, sedangkan produk efektif dilihat dari hasil uji coba. Hasil validasi para ahli memperoleh kriteria sangat valid dengan rerata 88,72%. Hasil angket respon mahasiswa memperoleh hasil sebesar 90,16% dengan kriteria sangat praktis. Hasil uji coba memperoleh nilai Sig. (2-tailed) uji t Paired adalah 0,000 lebih kecil dari 0,05 yang artinya terdapat kemampuan penalaran matematis mahasiswa sesudah menggunakan produk pengembangan berupa modul praktikum logika matematika berbasis PhET simulation. Dapat disimpulkan modul praktikum logika matematika berbasis PhET simulation layak digunakan sebagai panduan praktikum logika matematika dan dapat meningkatkan kemampuan penalaran mahasiswa.